Розробка компонентів інформаційної системи web сервісу онлайн оголошень - Шевченко, С. Р. (ХНУРЕ, 2024)
In the age of digital technologies, online ads have become a necessary tool for many users and businesses. They provide a convenient and fast way to find goods, services and jobs. Information systems that support these services require not only effective software, but also successful architecture and component development to ensure reliability, security, and user-friendliness. Modern information systems of online ads must meet a number of key requirements. First of all, it is the provision of a convenient user interface that allows you to easily interact with the system. Next, an important characteristic is the reliability and availability of the system, so that users can use the service at any time.
Keywords: web сервіс; онлайн оголошення